Effects of alternating stray current on the corrosion behaviours of buried Q235 steel pipelines. Issue 6 (6th November 2017) - Guo, Yanbao; Tan, Hai; Wang, Deguo; Meng, Tao
Abstract : Purpose: With the rapid development of rail transportation and energy-delivery systems, such as buried oil and gas pipelines and high-voltage transmission lines, the alternating current (AC) corrosion of buried steel pipelines is becoming more serious. This paper aims to study the corrosion behaviours of Q235 buried steel pipelines induced by the alternating stray current, with a set of indoor simulated experiment apparatuses. Design/methodology/approach: The corrosion of the coating holidays of the buried steel pipelines at various AC current densities from 0 to 200 A/m 2 in the soil-simulating environment was revealed by the electrochemical and weight-loss methods. Findings: The results showed that the corrosion potential of the steel shifted negatively obviously and the corrosion rate of the steel increased with the increasing of AC current density. At a low AC current density, the negative deviation of the corrosion potential of the steel was small and the increase of corrosion rate was slight. However, the negative deviation of the corrosion potential was remarkable and the corrosion rate was greatly increased at a relative higher AC current density. The geometrical shape of the corrosion images indicated the corrosion forms changed from uniform corrosion to local corrosion due to the increase of AC interference. Originality/value: Investigation results are of benefit to provide a new strategy to forecast and evaluate the AC-induced corrosion of the buried pipelines which could improve the safety of pipeline transportation.